Beckman Model R-112/R-115 Electrophoresis (1974)
Beckman introduced a Microzone Electrophoresis System in 1964; the Model R-112 was released in 1974. Electrophoresis uses an electric field to separate particles in a medium (like a gel) based on their size, charge, or a binding affinity.
Keywords: Electrophoresis; Scientific apparatus and instruments; Electrophoresis--Equipment and supplies; Beckman Instruments, Inc.